Diferença cultural nas diretrizes curriculares nacionais para o Ensino Fundamental: uma análise do discurso docente - Sousa, Jorge Luis Umbelino De (2018)
The cultural difference in curriculum policies has become a field of interest for many contemporary scholars. To do so, they develop studies and research that are anchored in differentiated perspectives that, for the moment, recognize the study of cultural identity and diversity, and at other times choose to analyze the difference in itself, without categorizing or specifying it. Thus, the present study has the objective of analyzing the meanings of cultural difference in curriculum policies, more precisely in the National Curriculum Guidelines for Elementary Education of 9 (nine) years and how teachers resignificate these meanings in their discursive practices in school. We are interested in the understanding that cultural difference is always a game of negotiation and translation, unable to be saturated in the original act and designator of identity, and therefore in an immeasurable dimension. That is why we continue to argue that curriculum policies are cultural policies demarcated by ambivalence and hybridity in times of re-contextualization. Such policies function as attempts to fix tentatively hegemonic and contingent meanings. In the contexts of schools they are interpreted and re-signified, since they present themselves as texts and discourses that produce slides of meanings and are open to heterogeneous and diversified reading. In this perspective, we opted for a theoretical-methodological dialogue anchored in a post-structuralist and postcolonialist movement of thought, interacting with BHABHA (1998), HALL (2003), DERRIDA (1991), BALL (1992; 1994), among other authors with which we were able to shift an understanding of educational policies that is based on a more ubiquitous approach to power and that would allow us to think the difference in the frontier times of new colonial authorities and discourses that restructure the relations between colonizer / colonized, I / Other. For the development of the analysis of both the text of the DCNEF and the teaching discourse, we operate with the Critical Discourse Analysis (ACD) of the British linguist FAIRCLOUGH (2001) in dialogue with the studies in the field of educational policies carried out by the British sociologist BALL (2012). With the ACD we were instigated to think of discourse as meaning of the world and discursive practice as situations of production and textual consumption, always involving processes of interpretation. Thus, the teachers' discourse points to the construction of meanings of cultural difference based on their reading of the DCNEF, constructing a semiosis that makes curriculum politics strained by the ambivalence of interpretation. Thus cultural difference appears in curriculum policies and in teaching discourses that cross them as the promise of equality / equity in which cultural groups will be included. However, it dissolves in this phantasmatic myth since at the moment of suturing an unrepresentable Other in this movement of recognition is always constitutive of the process, disturbing the very act of inclusion. The defense of respect for the Other can not, therefore, be exhausted in the search for a total control of the systems of signification, since "respecting" the cultural difference is not to stop the continuous flow of enunciation.